8x-11=13x+15

Simple and best practice solution for 8x-11=13x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-11=13x+15 equation:


Simplifying
8x + -11 = 13x + 15

Reorder the terms:
-11 + 8x = 13x + 15

Reorder the terms:
-11 + 8x = 15 + 13x

Solving
-11 + 8x = 15 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
-11 + 8x + -13x = 15 + 13x + -13x

Combine like terms: 8x + -13x = -5x
-11 + -5x = 15 + 13x + -13x

Combine like terms: 13x + -13x = 0
-11 + -5x = 15 + 0
-11 + -5x = 15

Add '11' to each side of the equation.
-11 + 11 + -5x = 15 + 11

Combine like terms: -11 + 11 = 0
0 + -5x = 15 + 11
-5x = 15 + 11

Combine like terms: 15 + 11 = 26
-5x = 26

Divide each side by '-5'.
x = -5.2

Simplifying
x = -5.2

See similar equations:

| 8.1-y=20 | | 18-x=(11+x)+3 | | 7x-7=2x-1 | | -2m-1=6m+1 | | 30000*12=x | | x^3-10x-21x=0 | | 4-2.5(x+5)=16 | | 5.8=x-72 | | 18-x=12+x | | 314=g+25 | | 6x-5(4x)=-42 | | 12+(-3h)=0 | | 89+x=100 | | 4x+3=2x-6 | | (-2x+3)+(5x-9)=24 | | 4x-5=2x-3 | | (8+3x)+(2-x)=14 | | (2x+10)+(3x-5)=90 | | 6x-14y=5 | | 175+.10m=125+.25m | | v-4=-18 | | 15x+7y=0 | | 6x^2-5=216 | | (2x+5)+(4x-1)=16 | | -8(r-2)=-10 | | 1.66+3n=.8n+18 | | T-32.8=-227 | | 6z-1/3=0 | | a-4b+c=3 | | -16x^2+1200= | | 12+4q=14+3q | | (x+13)(x+5)+2=0 |

Equations solver categories